A strategy for development of shallot Agribusiness Sub Terminal (STA) in Brebes. Issue 1 (September 2020) - Susanawati,; Fauzan, Muhammad; Widodo,
Abstract: This study aims were to (1) Identify internal and external factors that influence the development of shallot STA in Brebes Regency (2) Formulate a strategy for developing STA in Brebes Regency. The analytical method used in this study was a SWOT. The samples used in this study were 8 STA administrators, 2 Agriculture and Forestry Service Officers and 20 shallot farmers using the purposive sampling method. The results showed that the external factors that became an opportunity for the STA were the support from the government towards the STA, the number of shallot farmers in the regency of Brebes, the large number of food processing industries made from shallots. Moreover, the threat of the STA was the decline in farmer's land productivity, competitors provide selling stalls for farmers, and competitors provide capital for farmers and the large number of competitors spread in Brebes Regency. Three priority strategies for the development of the STA, namely cooperation with financial institutions, improve the organizational and optimize the use of stalls.